PENGARUH STRUKTUR MODAL, EFISIENSI OPERASIONAL, PERTUMBUHAN DAN MANAJEMEN ASET TERHADAP PROFITABILITAS DI BURSA EFEK INDONESIA - Anggita, Elvira Riska; Banjarnahor, Haposan (LPPM Universitas Putera Batam, 2021)
The current development of the economy requires companies to conduct important evaluations for investors to measure financial performance, namely profitability. Profitability is one of the company's measuring tools in generating profits. The purpose of this study was to determine the effect of capital structure, operational efficiency, growth and asset management on profitability in the Indonesia Stock Exchange. The independent variables are capital structure, operational efficiency, growth and asset management. In the population there are 45 companies in the banking sub sector which are listed on the Indonesia Stock Exchange. Purposive sampling is a sample collection technique into 18 companies. The data processing technique is using SPSS version 25. The method of data analysis uses multiple linear analysis. The results of the t test explain that the capital structure has a value of 1.289 which has a negative and insignificant effect of 0.211, operational efficiency has a value of 8.706 which has a negative and significant effect of 0.000, growth has a value of 0.675 which has a negative and insignificant effect of 0.513, management assets have a value of 1.358 which has a negative and insignificant effect of 0.178. The results of the hypothesis test explain that Fcount23.551> Ftabel 2.48 and the significant level F is 0.000 < 0.05.